Perspectives on Research Paradigms: A Guide for Education Researchers - Alhoussawi, Hussain (International Research in Education, 2023)
This scholarly article undertakes a thorough exploration of current theoretical perspectives within the domain of educational research, concentrating specifically on the positivist, interpretive, and critical paradigms. It commences by establishing a comprehensive understanding of research within the larger context, with a particular spotlight on educational research and its central paradigms. The manuscript subsequently provides a concise yet illuminating examination of these three primary research paradigms, shedding light on their ontological, epistemological, and methodological dimensions. Additionally, it conducts an evaluation of each paradigm based on criteria pertinent to rigorous research, thereby accentuating their individual merits and shortcomings. The positivist paradigm, firmly grounded in empiricism, places a strong emphasis on empirical evidence and the systematic application of the scientific method to reveal objective truths and establish causal relationships. It is renowned for its unwavering dedication to objectivity, quantifiability, and the potential for broad generalization, frequently making use of hypothesis testing and experimental methodologies. Despite facing criticism for its potential to oversimplify intricate phenomena, positivism continues to maintain its predominance across a wide array of fields. The interpretive paradigm, firmly rooted in hermeneutics, places a primary emphasis on the investigation of subjective meanings and the realm of human experiences. This paradigm utilizes qualitative research methods to deeply explore the intricacies of individuals' perspectives, recognizing researchers as active interpreters of the collected data. Interpretive research emerges as highly valuable in the examination of areas such as cultural practices, the development of identities, and social interactions. The critical paradigm, drawing from interpretive principles as its foundation, rigorously examines power dynamics and matters of social justice. Through the use of qualitative research methods, it thoroughly explores structural inequalities and issues related to equity, demonstrating particular relevance in situations that demand a comprehensive assessment and active intervention in systemic injustices.